Attributable costs and length of stay of hospital-acquired Clostridioides difficile: A population-based matched cohort study in Alberta, Canada. (25th July 2019) - Leal, Jenine R.; Conly, John; Weaver, Robert; Wick, James; Henderson, Elizabeth A.; Manns, Braden; Ronksley, Paul
Abstract: Objective: To determine the attributable cost and length of stay of hospital-acquired Clostridioides difficile infection (HA-CDI) from the healthcare payer perspective using linked clinical, administrative, and microcosting data. Design: A retrospective, population-based, propensity-score–matched cohort study. Setting: Acute-care facilities in Alberta, Canada. Patients: Admitted adult (≥18 years) patients with incident HA-CDI and without CDI between April 1, 2012, and March 31, 2016. Methods: Incident cases of HA-CDI were identified using a clinical surveillance definition. Cases were matched to noncases of CDI (those without a positive C. difficile test or without clinical CDI) on propensity score and exposure time. The outcomes were attributable costs and length of stay of the hospitalization where the CDI was identified. Costs were expressed in 2018 Canadian dollars. Results: Of the 2, 916 HA-CDI cases at facilities with microcosting data available, 98.4% were matched to 13, 024 noncases of CDI. The total adjusted cost among HA-CDI cases was 27% greater than noncases of CDI (ratio, 1.27; 95% confidence interval [CI], 1.21–1.33). The mean attributable cost was $18, 386 (CAD 2018; USD $14, 190; 95% CI, $14, 312–$22, 460; USD $11, 046-$17, 334). The adjusted length of stay among HA-CDI cases was 13% greater than for noncases of CDI (ratio, 1.13; 95% CI, 1.07–1.19), which corresponds to an extra 5.6 days (95% CI, 3.10–8.06) in length of hospital stay per HA-CDI case. Conclusions: In this population-based, propensity score matched analysis using microcosting data, HA-CDI was associated with substantial attributable cost.